TURISMO UN APORTE AL BUEN VIVIR COMUNITARIO EN TERRITORIOS ANDINOS RURALES ECUATORIANOS. ESTUDIO DE CASO: QHAPAQ ÑAN - PISTISHÍ - NARIZ DEL DIABLO - Vizuete, Danny Castillo; Merino, Christiam Aguirre; Cañizares, Fernando Romero (European Scientific Journal, ESJ, 2015)
Ecuador has high biodiversity, and is a multiethnic and multicultural country, where unique experiences can occur, all reasons for high potential for tourism. Within Ecuador’s history, there exists a recent change in the economy in which tourism is immersed. Pistishí is a rural parish that is located in the south of the canton of Alausí, province of Chimborazo, formed of two communities of mixed indigenous groups: Tolte and Achaisí. The archeological route Qhapaq Ñan and the railway site of the Nariz del Diablo are a part of the natural and cultural patrimony of the country, among other attractions that have not yet been exploited for tourism in Pistishí. Based on the current potential of the territory for tourism, on an acceptable forecast of future demand, and on the capacity of the community to organize, tourist packages are designed and offered in the rural Andean territories for sale to visitors. These packages incorporate commercial, artisanal, agricultural and recreational activities. In conclusion, tourism streamlines the communitarian economy, with a focus on the mixture of cultures as the basis for Buen Vivir.